Editor’s Letter - Sánchez Gutiérrez, José (Mercados y Negocios, 2025)
Welcome to the 54th issue of our journal, where we present diverse research articles that delve into contemporary issues across various fields. This issue combines empirical studies and theoretical explorations illuminating different aspects of business, tourism, food preferences, and organizational culture. We aim to provide insightful analyses and foster a deeper understanding of these multifaceted topics.